Collaborative Governance Dalam Pengembangan Kampung Wisata Dalam Mengatasi Persoalan Kumuh Di Kota Tangerang - Irvan Arif Kurniawan; Ida Widianingsih; Sinta Ningrum Wiradinata; Sam’un Jaja Raharja (Aliansi, 2022)
A tourism village is a concept to improve the socio-economic conditions of a community. The concept of a tourist village in Tangerang City is a breakthrough in creating local tourist destinations to create a livable and worthy city to visit. The concept of a tourist village is one of the efforts to overcome the problem of slums in Tangerang City. The slum problems in Tangerang City have become a central issue for the last 4 (four) years. In order to overcome the slum problem through the concept of a tourist village, it cannot be done by the government alone but requires the role of other stakeholders such as the role of the private and public. The collaborative governance model is an integrated model by connecting organizations across formal and informal boundaries. The collaborative governance model emerged as a response to increasingly complex public problems. Collaborative governance model According to Ansell & Gash consists of: face-to-face dialogue, trust-building, commitment to the process, shared understanding, and intermediate outcomes. Collaborative governance can be the solution in overcoming the slums problem in Tangerang City by developing tourist villages.